(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This study aims to determine the dimensions of strategic Entrepreneurship and its impact on achieving excellence performance. The problem of the study revolves around the role of strategic Entrepreneurship dimensions in the success of the work of tourism organizations, as well as in achieving excellence performance. To achieve the aim of the study, a methodology was formulated that required building a hypothetical scheme that reflects the influence relationships between the dimensions of strategic Entrepreneurship in achieving performance excellence, which results in a set of key hypotheses that reflect the validity of those relationships. The study relied on a set of statistical tools and methods that were used to analyze the data. The study reached a number of conclusions, the most important of which That strategic Entrepreneurship in its dimensions is a concept that increases work efficiency and also works to reduce financial costs and other available resources.